1984
DOI: 10.1136/bmj.289.6446.648
|View full text |Cite
|
Sign up to set email alerts
|

Red cell ferritin content: a re-evaluation of indices for iron deficiency in the anaemia of rheumatoid arthritis.

Abstract: In iron deficiency anaemia basic red cell content of ferritin is appreciably reduced. This variable was determined in 62 patients with rheumatoid arthritis to evaluate conventional laboratory indices for iron deficiency in the anaemia of rheumatoid arthritis.For 23 patients with rheumatoid arthritis and normocytic anaemia irrespective of plasma ferritin concentration, red cell ferritin content did not differ significantly from that for non-anaemic patients with rheumatoid arthritis. For 27 patients with rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Clinical and biological studies suggested that eryth roblast ferritin synthesis depends on the balance between iron supply to the erythroblast and its utilization for Hb production [12][13][14], Previous studies have shown that in some pathological conditions, such as rheumatoid arthri tis and liver disease, EF could be more useful than other parameters to assess the body iron status [15,16], In this study we showed that in CHD patients both EF and SF were scattered over a wide range. A little group of CHD patients (table 1, group 3) had a consensual increase of EF and SF values in comparison with nonnephropathic sub jects: they had been frequently transfused or treated with parenteral iron in the past and an iron overload was likely to be present.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Clinical and biological studies suggested that eryth roblast ferritin synthesis depends on the balance between iron supply to the erythroblast and its utilization for Hb production [12][13][14], Previous studies have shown that in some pathological conditions, such as rheumatoid arthri tis and liver disease, EF could be more useful than other parameters to assess the body iron status [15,16], In this study we showed that in CHD patients both EF and SF were scattered over a wide range. A little group of CHD patients (table 1, group 3) had a consensual increase of EF and SF values in comparison with nonnephropathic sub jects: they had been frequently transfused or treated with parenteral iron in the past and an iron overload was likely to be present.…”
Section: Discussionmentioning
confidence: 82%
“…For these reasons, EF may be a useful parameter to disclose the real iron need in patients with increased or reduced red cell turnover. Moreover, EF seems to be scarcely influenced by those factors such as liver cell necrosis [15] or inflammatory diseases [16] that may specifically increase SF levels [7], To our knowl edge, no data on EF behavior in CHD patients are pres ently available. In this study, we evaluated EF levels in 35 patients on CHD with different body iron stores assessed according to SF levels.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the usual lower limits of normal for this assay (12-15 ng/ml) should be adjusted in these settings to compensate for this recognized difference. Recommended adjusted cutoff levels for SERFER have vaned from 50 to 110 ng/ml [6,9,22,23]. In spite of such modifications, the evaluation of iron stores in these common clinical states continues to be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the basic (hepatic/spleen type) ferritin fraction remains unchanged throughout the red cell lifespan [ 101. For this reason it has been proposed that a RBCFER measurement may represent a stable protein and thus may be a more effective tool in assessing iron stores in chronic disease [ 141, rheumatoid arthritis [22], and liver disease [13,24].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration tends to vary inversely with the red cell protoporphyrin concentration (107). Thus in patients with rheumatoid arthritis and anaemia, a low concentration is found in those with microcytosis, and a low serum iron concentration is observed regardless of the serum ferritin concentration (109). The red cell ferritin concentration does not therefore necessarily indicate the concentration of iron in storage.…”
Section: Red Cell Ferritin and Its Diagnostic Usementioning
confidence: 97%